Decoding m6A mRNA methylation by reader proteins in liver diseases - Lijiao Sun; Xin Chen; Sai Zhu; Jianan Wang; Shaoxi Diao; Jinyu Liu; Jinjin Xu; Xiaofeng Li; Yingyin Sun; Cheng Huang; Xiaoming Meng; Xiongwen Lv; et al. (Genes and Diseases, 2024)
N6-methyladenosine (m6A) is a dynamic and reversible epigenetic regulation. As the most prevalent internal post-transcriptional modification in eukaryotic RNA, it participates in the regulation of gene expression through various mechanisms, such as mRNA splicing, nuclear export, localization, translation efficiency, mRNA stability, and structural transformation. The involvement of m6A in the regulation of gene expression depends on the specific recognition of m6A-modified RNA by reader proteins. In the pathogenesis and treatment of liver disease, studies have found that the expression levels of key genes that promote or inhibit the development of liver disease are regulated by m6A modification, in which abnormal expression of reader proteins determines the fate of these gene transcripts. In this review, we introduce m6A readers, summarize the recognition and regulatory mechanisms of m6A readers on mRNA, and focus on the biological functions and mechanisms of m6A readers in liver cancer, viral hepatitis, non-alcoholic fatty liver disease (NAFLD), hepatic fibrosis (HF), acute liver injury (ALI), and other liver diseases. This information is expected to be of high value to researchers deciphering the links between m6A readers and human liver diseases.